Decision Analysis for Selecting Steam Boiler Units in the Detergent Manufacturing Industry Using the Delphi, DEMATEL, and ANP Methods (Case Study: PT. XYZ) - Samantha, Hendra Rahadian; Widodo, Erwin (Syntax Corporation, 2025)
Boilers are vital components in the manufacturing industry because they give the heat energy required for industrial processes. The main boiler unit at PT. XYZ has been in use for over 42 years and is exhibiting decreased efficiency as well as increased safety risks. To address these issues, the company plans to upgrade the existing system with a new boiler with a larger capacity. The selection of boiler units has traditionally been guided solely by the lowest price, without consideration for energy efficiency, safety, environmental concerns, or technological needs all of which can significantly increase operating costs and production interruption risks. This study uses a Multi Criteria Decision Making (MCDM) approach to develop an objective and data driven decision making framework using the Delphi technique, Decision Making Trial and Evaluation Laboratory (DEMATEL), and the Analytic Network Process (ANP). The most significant sub criteria in boiler selection are Boiler Efficiency at 100% Load Specific Energy, which has a weight of 11,83%, followed by Initial Investment Cost (10,84%) and Boiler Safety Control System (10, 13%). The Yuanda Boiler was given the greatest priority weight of 0,349374 among the four evaluated options and is therefore recommended as the best choice, followed by the Miura Boiler (0,319063), the Erensen Boiler (0,196042), and the Omnical Boiler (0,13552). The model established in this work offers a clear and comprehensive decisionmaking framework that can help management choose the best boiler investment that is both energy efficient and sustainable.